An In‐Situ NMR Study of Radical Copolymerization Kinetics of Acrylamide and Non‐Ionized Acrylic Acid in Aqueous Solution. Issue 1 (November 2013) - Preusser, Calista; Hutchinson, Robin A.; Moritz, Hans‐Ulrich; Pauer, Werner
Summary An in‐situ NMR technique has been developed to study the aqueous phase copolymerization of non‐ionized acrylic acid (AA) and acrylamide (AM) under near‐isothermal conditions at much higher monomer contents than previously reported in the literature. The composition data obtained over the entire conversion range provides a precise estimate of monomer reactivity ratios not available from low conversion data. The set of experiments, with initial monomer content in aqueous solution varied between 5 and 40%, were well‐fit over the complete conversion range by rAA = 1.24 ± 0.02, and rAM = 0.55 ± 0.01. It was found that the rate of monomer conversion increases with increasing monomer concentration, a trend contrary to the known decrease in the AA and AM chain‐end propagation rate coefficients.